Retention of Balinese Agricultural Vocabulary in Jati Bali Village, South Konawe Regency: Kebertahanan Kosakata Pertanian Bahasa Bali di Desa Jati Bali, Kabupaten Konawe Selatan - Ni Gusti Agung Ketut Tri Wahyuni; Sri Suryana Dinar; La Tike (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2026)
Declining mastery of regional-language vocabulary among young speakers indicates a vulnerable point in the intergenerational transmission of ecological knowledge. This study describes the retention of Balinese agricultural lexicon among young Balinese speakers in Jati Bali Village, South Konawe Regency. The study used field research with descriptive quantitative analysis interpreted qualitatively through an ecolinguistic perspective. Data were collected from 50 respondents aged 17-25 years through a questionnaire containing 75 Balinese agricultural lexical items categorized into plant names, animal names, agricultural tools, and farming activities. The findings show that 2,213 of 3,750 responses (59.01%) were actively known and used, 463 responses (12.35%) were known passively, and 1,074 responses (28.64%) were unknown. Plant vocabulary had the strongest retention (74.67%), followed by animal vocabulary (66.37%), tool vocabulary (48.33%), and farming-activity vocabulary (39.44%). The study concludes that lexical retention depends on visible referents, continued agricultural practice, family transmission, and ecological-cultural continuity. This study contributes to ecolinguistic documentation and regional-language maintenance in migrant Balinese communities.